2020
DOI: 10.1111/jcmm.15105
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of ATP2B1‐AS1 contributes to protection against myocardial infarction in mouse via blocking NFKBIA‐mediated NF‐κB signalling pathway

Abstract: Myocardial infarction (MI) is an acute coronary syndrome that refers to tissue infarction of the myocardium. This study aimed to investigate the effect of long intergenic non-protein-coding RNA (lincRNA) ATPase plasma membrane Ca 2+ transporting 1 antisense RNA 1 (ATP2B1-AS1) against MI by targeting nuclear factor-kappa-B inhibitor alpha (NFKBIA) and mediating the nuclear factor-kappa-B (NF-κB) signalling pathway. An MI mouse model was established and identified by cardiac function evaluation. It was determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 46 publications
(48 reference statements)
6
23
0
Order By: Relevance
“…The potential neuroprotective effect of ATP2B1-AS1 on the cerebral I/R injury in MCAO/IR rats and OGD/R PC12 cells were explored in our study. As reported in a previous study, ATP2B1-AS1 was highly expressed in mice with myocardial infarction, while silencing of mouse ATP2B1-AS1 reduced cardiomyocyte apoptosis and inhibited the expression of inflammatory cytokines, as well as promoted the cardiomyocyte viability (Song et al, 2020). In this study, we confirmed that the expression of ATP2B1-AS1 was upregulated in a MCAO/IR rat model and OGD/R PC12 cells with a time independent manner.…”
Section: Discussionsupporting
confidence: 89%
“…The potential neuroprotective effect of ATP2B1-AS1 on the cerebral I/R injury in MCAO/IR rats and OGD/R PC12 cells were explored in our study. As reported in a previous study, ATP2B1-AS1 was highly expressed in mice with myocardial infarction, while silencing of mouse ATP2B1-AS1 reduced cardiomyocyte apoptosis and inhibited the expression of inflammatory cytokines, as well as promoted the cardiomyocyte viability (Song et al, 2020). In this study, we confirmed that the expression of ATP2B1-AS1 was upregulated in a MCAO/IR rat model and OGD/R PC12 cells with a time independent manner.…”
Section: Discussionsupporting
confidence: 89%
“…The silencing of IRAK3 inactivated the NF-κB signalling pathway, thereby attenuating the progression of AMI in mice 11. The silencing of ATP2B1-AS1 had a protective effect post-MI by blocking the NF-κB pathway 30. In our study, knockdown of circ_0060745 suppressed the expressions of IL-6, IL-12, IL-1β, TNF-α and NF-κBp65 under hypoxia.…”
supporting
confidence: 50%
“…The protein encoded by nfkbia was identified as a target for glucocorticoid-mediated immunosuppression (54). In mice, nfkbia was poorly expressed and the NF-kB signaling pathway was activated during myocardial infarction, while overexpression of nfkbia reduced the expression of inflammatory cytokines and cardiomyocyte apoptosis, and improved cardiomyocyte viability (55). Because map3k7cl was downregulated in Chinese patients with non-small cell lung cancer, Niu et al speculated that map3k7cl in the leukocytes may contribute to pathogenesis via reducing inflammatory processes, regulating mitochondrial reactive oxygen species signaling, and mediating the Wnt pathway (56).…”
Section: Discussionmentioning
confidence: 99%